Family Ownership, Women in Top Management and Risk-Taking: Evidence from Indonesia - Novi Widyawati; Irwan Trinugroho; Wisnu Untoro (Jurnal Keuangan dan Perbankan, 2018)
Family firms were widely recognized to have a substantial contribution to the economy, especially in emerging economies. However, some previous studies reveal that family firms tend to be conservative and unwilling to take more risks. We extended the literature by investigating whether there was a difference in risk-taking behavior between family and non-family firms in the context of Indonesia. Moreover, the presence of women in the top management also considered negatively correlated with risk-taking strategy. Therefore, this study empirically examined the effects of family ownership and women in top management on a risk-taking strategy of firms. Using data of 336 publicly traded firms in Indonesia over 2012-2016, this study confirmed the negative effect of family ownership and women in top management on corporate risk-taking. Family ownership and involvement as the CEO of the firms negatively associated with the level of risk taking. Moreover, our results reveal that the presence of women was a matter more to decrease corporate risk-taking when they served in the board of directors rather than in the board of commissioners.JEL Classification: G32, M14DOI: https://doi.org/10.26905/jkdp.v22i4.2452